"ﺎحﻟ تادﺎﺷراﻻو ﺲﻔﻨﻟا ﻢﻠﻋو مﻼﺳاﻻ. - Dahlan, Juwairiyah (Proceedings of International Conference on Muslim Society and Thought, 2017)
" ﺎحﻟ تادﺎﺷراﻻو ﺲﻔﻨﻟا ﻢﻠﻋو مﻼﺳاﻻ. Juwairiyah Dahlan, UIN Sunan Ampel Surabaya. "